Aglaya Returns Home, The Mystery of The Apocryph of Aglaia. Ed. by Elena Kozmina. INTMEDIA, Yekaterinburg 2020, 231 pp. ISBN 978-5-6040560-8-0 - Pálfalvi, Lajos (Slavica, 2022)
This collection of studies is a unique example of a collective monograph written by Russian, Polish and Hungarian scholars on a contemporary Polish literary work. The novel by Jerzy Sosnowski entitled Aglaia’s Apocrypha is an ideal subject of analysis because of its complicated narrative structure, multilevel composition and genre complexity. The authors of the studies describe the connections between the storytellers and the author, define the context of the novel both in high and popularculture. Some of them represent the best traditions of Russian poetics of prose. Jerzy Sosnowski began his career as a literary critic and literary historian, he was an influential interpreter and promoter of the new tendencies in the Polish literature of the eighties.When he became a prosewriter, he followed the new aesthetic trend of Polish postmodernism. Jerzy Sosnowski as the author of a novel written about an erotic cyborg, its/her admirer and the operator was a forerunner of posthumanism.